The Combined Model of CX3CR1-Related Immune Infiltration Genes to Evaluate the Prognosis of Idiopathic Pulmonary Fibrosis - Cai, Haozheng; Chen, Shijie; Li, Xinyu; Liu, Hanying; Zhang, Ying; Zhuang, Quan (Frontiers in Immunology, 2022)
Background High expression of chemokine (C-X3-C motif) receptor 1 (CX3CR1) was shown to contribute to the progression of many fibrotic diseases. However, there is still no study for the role of CX3CR1 in idiopathic pulmonary fibrosis (IPF). Therefore, we aimed to identify CX3CR1-related immune infiltration genes (IIGs) in IPF and establish a combined risk model to evaluate the prognosis of IPF. Methods A discovery cohort of IPF patients (GSE70867) was downloaded from the Gene Expression Omnibus dataset. We identified the composition of 22 kinds of immune cells infiltration by CIBERSORT. The Cox regression model with the LASSO method was used for identifying prognostic genes and developing CX3CR1-related IIGs. Kaplan–Meier was applied to plot the survival curve of prognosis model. Peripheral blood mononuclear cell (PBMC) and bronchoalveolar lavage fluid (BALF) were collected to be tested by quantitative reverse transcriptase-PCR (qRT-PCR) from 15 clinical samples, including 8 healthy controls (HC), 4 patients with usual interstitial pneumonia (UIP) and 3 patients with pulmonary fibrosis (FIB). Results We found that high expression of CX3CR1 in BALF contributed to the poor prognosis in IPF patients. ALR4C, RAB37, GPR56, MARCKS, PXN and RASSF2 were identified as CX3CR1-related IIGs, which were highly expressed in PBMC of UIP/FIB patients than that of HC. Moreover, the expression of PXN was higher in FIB patients’ PBMC than that of UIP ones. In the cohort of IPF patients, high infiltration of activated NK cells in BALF caused poor survival compared to low infiltration group. The infiltration of activated NK was regulated by CX3CR1-related IIGs. The combined risk model predicted that high expression of CX3CR1-related IIGs and high infiltrated activated NK cells caused poor prognosis in IPF patients. Conclusion We identified a group of CX3CR1-related IIGs in IPF patients. This combined risk model provided new insights in the prognosis and therapy of IPF.